The Economics of Money, Banking and Financial Markets - Frederic S. Mishkin (United Kingdom Pearson Education Limited, 2022)
For courses in money and banking, or general economics. A unified framework for understanding financial markets The Economics of Money, Banking and Financial Markets bringsa fresh perspective to today's major questions surrounding financial policy.Influenced by his term as Governor of the Federal Reserve, Frederic Mishkinoffers students a unique viewpoint and informed insight into the monetarypolicy process, the regulation and supervision of the financial system, and theinternationalization of financial markets. The 13th Edition providesa unifying, analytical framework for learning that fits a wide variety ofsyllabi. And core economic principles and real-world examples organizestudents' thinking and keep them motivated. After reading this text, studentsare well equipped to apply these financial models, terms, and equations todecisions that affect both their personal and professional lives.
Keywords: Economics; Money; Finance; Business; Textbooks; Banking; (MGT-104) Fundamentals of Financial Decision-Making; (APC-312) Money, Banking and Finance; (APC-313) Financial markets